The attitudes of deaf adults in the area of Johannesburg to writing English as a second or third language. - Morgans, Helen Guinevere (My University, 2010)
This research investigates the attitudes of adult Deaf South Africans, in the area of Johannesburg, to writing in English in their daily lives. The research intends to explain the concept that signed language, i.e. South African Sign Language (SASL), is different from spoken or written languages and has its own grammatical structure. It also has no written form. Deaf people are therefore a linguistic minority who have to read and write in a second or third language, in this case, English. Deaf people do not have automatic access to spoken and written languages. Schools of Deaf children today do not use SASL as a medium of instruction although this is in contravention of the South African Schools Act (1996). Because of their inability to hear, it is more difficult for Deaf people to acquire spoken English and this further complicates access to literacy in English. According to the Deaf Federation of South Africa (DeafSA) (1997), the average reading and writing level of Deaf adults is at the fourth grade. Even Deaf adults, who can read and write, often lack confidence to write in both professional and social settings. This research sets out to understand when, and if, they feel secure about writing and what strategies they use to manage their writing needs. In addition, many Deaf people who have barely acquired schooled literacy cope well in mainstream society. In order to understand how they accommodate to the demands of literacy, the study draws from research in New Literacy Studies (NLS) and argues, along with Street (1984) that literacy is acquired through processes of informal learning and sense making in social settings. By analysing responses to a Likert Scale questionnaire to semi-structured interviews and by a linguistic analysis of participants’ writing, this research aims to understand Deaf people’s writing and their literacy practices. This understanding will enable mainstream society, including hearing educators of Deaf learners, subject advisors and policy makers in the National and Provincial Departments of Education and professional people working with Deaf people to understand the challenge that literacy presents. In addition, it will also enable Deaf people to understand other Deaf people’s attitude to writing. This research documents the relationship Deaf adults have with writing, and produces findings which can be used for literacy curriculum development in mainstream schools, schools of Deaf children and universities. One of its aims is to provide information for hearing people with responsibility for the education of Deaf people.